Cryptosporidium parvum Elongation Factor 1α Participates in the Formation of Base Structure at the Infection Site During Invasion. (24th December 2019) - Yu, Xue; Guo, Fengguang; Mouneimne, Rola Barhoumi; Zhu, Guan
Abstract: Background: Cryptosporidium is a genus of apicomplexan parasites, the causative agents of cryptosporidiosis in humans and/or animals. Although most apicomplexans parasitize within the host cell cytosols, Cryptosporidium resides on top of host cells, but it is embraced by a double-layer parasitophorous vacuole membrane derived from host cell. There is an electron-dense band to separate the parasite from host cell cytoplasm, making it as an intracellular but extracytoplasmic parasite. However, little is known on the molecular machinery at the host cell-parasite interface. Methods: Cryptosporidium parvum at various developmental stages were obtained by infecting HCT-8 cells cultured in vitro. Immunofluorescence assay was used to detect CpEF1α with a polyclonal antibody and host cell F-actin with rhodamine-phalloidin. Recombinant CpEF1α protein was used to evaluate its effect on the invasion by the parasite. Results: We discovered that a C parvum translation elongation factor 1α (CpEF1α) was discharged from the invading sporozoites into host cells, forming a crescent-shaped patch that fully resembles the electron-dense band. At the same time, host cell F-actin aggregated to form a globular-shaped plug beneath the CpEF1α patch. The CpEF1α patch remained for most of the time but became weakened and dissolved upon the completion of the invasion process. In addition, recombinant CpEF1α protein could effectively interfere the invasion of sporozoites into host cells. Conclusions: CpEF1α plays a role in the parasite invasion by participating in the formation of electron-dense band at the base of the parasite infection site. Abstract : Cryptosporidium is an intracellular but extracytoplasmic parasite separate from host cell by a unique pedestal structure. In this study, a Cryptosporidium protein (EF1α) was discovered to participate in the formation of the pedestal during parasite invasion into host cells.